Effect of Chinese Patent Medicines on Ocular Fundus Signs and Vision in Calcium Dobesilate-Treated Persons With Non-Proliferative Diabetic Retinopathy: A Systematic Review and Meta-Analysis - Zhang, Yuehong; An, Xuedong; Duan, Liyun; Jin, De; Duan, Yingying; Zhou, Rongrong; Zhang, Yuqing; Kang, Xiaomin; Lian, Fengmei (Frontiers in Endocrinology, 2022)
Background: Diabetic retinopathy (DR), one of the commonest microvascular complications in diabetic patients, is featured by a series of fundus lesions. Conventional Western medicine therapies for DR are always with modest treatment outcome. This paper is to assess the ocular fundus signs, vision and safety of Chinese patent medicines (CPMs) as an add-on treatment for DR. Method: 7 electronic databases were searched to determine eligible trials. Randomized controlled trials (RCTs) of non-proliferative diabetic retinopathy (NPDR) in which the intervention group received CPMs combined with calcium dobesilate (CD) and the control group received only CD were included for analysis. Two reviewers extracted the data independently. Results expressing as mean differences (MD) and relative risks (RR) were analyzed with a fixed-effects or random-effects models. Results: 19 RCTs involved 1568 participants with 1622 eyes met our inclusion criteria. The results suggested that compared with CD alone, CPMs plus CD for NPDR was superior at reducing the microaneurysm volume (MD -3.37; 95% confidence interval [CI], -3.59 to -3.14), microaneurysm counts (MD -2.29; 95%CI -2.97 to -1.61), hemorrhage area (MD -0.79; 95%CI -0.83 to -0.75), and macular thickness (MD -59.72; 95%CI -63.24 to -56.20). Participants in CPMs plus CD group also achieved a better vision. No obvious adverse events occurred. Conclusion: CPMs as an add-on therapy for NPDR have additional benefits and be generally safe. This meta‐analysis demonstrated that CPMs combined with CD could improve retinal microaneurysm, hemorrhage, macular thickness, visual acuity, fasting blood glucose (FBG), and glycosylated hemoglobin (HbAlc) compared with CD alone. Further studies are needed to provide more conclusive evidence.